A febre das apostas: como as apostas esportivas estão mudando a vida dos brasileiros - Sono, Gustavo Martins (2025)
The present study aims to analyze the phenomenon of sports betting in Brazil, its development following recent legal regulation, and its economic, social, and behavioral impacts. The research is based on a bibliographic review, the analysis of market data, and the examination of recent legislation, with the objective of understanding how this practice has become a relevant industry while simultaneously presenting ethical and regulatory challenges. The study discusses the expansion of the sports betting market, its effects on the mental health of bettors, the impact on the national sports landscape, and the necessity of effective public policies to ensure consumer protection. The study concludes by offering recommendations for the improvement of regulatory mechanisms and the promotion of a responsible gambling culture.